Red fluorescence anisotropic conductive film capable of preventing counterfeiting and encrypting information
By using biaxial parallel electrospinning technology to prepare [Pb-MOF/Eu-MOF/PMMA]//[CNTs/PMMA] Janus fiber array films, the problem of combining fluorescence and conductivity was solved, realizing the multifunctional application of red fluorescent anisotropic conductive films, and possessing optical information storage encryption and dual-wavelength optical anti-counterfeiting capabilities.
Patent Information
- Application Number
- CN202511241394.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-02
- Publication Date
- 2025-11-14
AI Technical Summary
Existing technologies struggle to achieve a good combination of fluorescence and conductivity in a single material, especially during the blending process, which can easily lead to a decrease in luminescence intensity or a decline in conductivity, failing to meet the application requirements of multifunctional materials.
Using biaxial parallel electrospinning technology, Eu-MOF and Pb-MOF were assembled into different regions of Janus fibers, and CNTs were assembled into another region. Using PMMA as a matrix, a [Pb-MOF/Eu-MOF/PMMA]//[CNTs/PMMA] Janus fiber array film was prepared to achieve microscopic integration of fluorescence and conductivity properties.
A red fluorescent anisotropic conductive film with excellent fluorescence and conductivity was obtained, realizing optical information storage encryption and dual-wavelength optical anti-counterfeiting functions, and possessing good anti-counterfeiting performance.
Smart Images

Figure CN120945584A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fiber material preparation technology, specifically to a red fluorescent anisotropic conductive film with anti-counterfeiting and information encryption capabilities and its preparation technology. Background Technology
[0002] Anisotropic conductive films are a new type of interconnect material for electronic components. They have conductivity in one direction and insulation in other directions, and have been widely used in electronic packaging, chip fixing and electrode bonding, attracting great attention.
[0003] Single-function materials have limited applications, while dual-function or multi-function materials have a wider range of applications. These materials are more distinctive and attractive, thus multi-function materials have attracted significant attention from researchers. With the development of science and technology, materials are evolving from single-function materials, such as those with luminescent, conductive, or magnetic properties, towards dual-function and multi-function materials, such as those with magneto-optical, opto-electric, or electromagnetic dual functions. This allows for the realization of dual or multi-function properties within a single material, which is of great significance to the development of related science and technology. For example, magnetic-fluorescent dual-function materials provide a new platform for disease diagnosis and treatment, as their dual-function properties integrate disease "discovery-detection-treatment." The use of such materials will further improve diagnostic efficiency and reduce side effects, attracting significant attention from researchers. Fluorescent / magnetic / conductive dual-function materials have broad application prospects in fields such as luminescence and display, anti-counterfeiting encryption, antistatic coatings, electromagnetic interference shielding, microwave absorption, sensors, and multi-functional devices. If fluorescent / magnetic / conductive dual-function materials also possess anti-counterfeiting and information storage encryption functions, such new materials will have important and broader application prospects, but this has not yet been reported.
[0004] Janus materials refer to materials in which two chemical components have a clearly defined partitioned structure within the same system, thus exhibiting dual properties such as hydrophilic / hydrophobic, polar / nonpolar, and luminescent / conductive. This represents an important research direction in materials science. Janus fibers, on the other hand, are fibers in which two chemical components have a clearly defined partitioned structure within the same fiber, possessing two or more properties. For example, one side of the fiber may have luminescent properties, while the other side may have conductive properties. Two fibers adhere side-by-side to form a Janus fiber. With a special receiving device, these Janus fibers can be oriented to form a Janus fiber array. This novel Janus fiber array membrane, possessing both fluorescent and conductive functions, has broad application prospects.
[0005] Metal-organic frameworks (MOFs) have broad application prospects in many fields due to their unique structure and properties. Rare earth metal europium ions (Eu) 3+Europium readily forms a metal-organic framework (MOF) with pyromellitic acid (H4BTC), known as Eu-MOF. Due to the unique electronic configuration of europium ions, it becomes a luminescent material with distinctive properties, such as high luminescence intensity, good stability, high fluorescence quantum yield, and good monochromaticity. It is a widely used fluorescent material, emitting bright red fluorescence under ultraviolet light at 254 nm and 272 nm. Lead ions (Pb) 2+ Pb-MOF readily forms a metal-organic framework with pyromellitic acid (H3BTC), which readily reacts with CsBr to generate green fluorescent CsPbBr3 perovskite quantum dots, applicable to anti-counterfeiting and information storage encryption. Carbon nanotubes (CNTs), as highly conductive fillers, are widely used in various composite conductive materials. Polymethyl methacrylate (PMMA) is a commonly used polymer material with excellent performance. Therefore, constructing a red fluorescent anisotropic conductive film with anti-counterfeiting and information encryption capabilities using Eu-MOF, Pb-MOF, CNTs, and PMMA is an ideal choice.
[0006] Existing research indicates that directly blending black CNTs with luminescent Eu-MOFs significantly reduces the luminescence intensity of Eu-MOFs. Furthermore, directly blending insulating Eu-MOFs and Pb-MOFs with CNTs causes the insulating Eu-MOFs and Pb-MOFs to disperse between CNTs, increasing the distance between them and disrupting the continuous conductive network, thus significantly reducing conductivity. Therefore, to obtain bifunctional materials with both good fluorescence and conductivity, the following two points must be achieved: (1) Dark-colored conductive CNTs cannot be directly blended with Eu-MOFs and must be effectively separated; (2) CNTs must be continuously distributed in the matrix, and insulating Eu-MOFs and Pb-MOFs cannot be directly blended with conductive CNTs and must be effectively separated. Therefore, for multifunctional materials, designing and constructing suitable building blocks is crucial. One-dimensional Janus fibers have two independent partitions, which can assemble Eu-MOF and Pb-MOF in one region and CNTs in another region. This achieves a high degree of integration of the two functions at the microscopic level, while keeping them independent of each other. This reduces the adverse interaction between fluorescence and conductivity. In other words, the one-dimensional Janus fiber structure achieves the above two requirements, thereby obtaining a high-performance optoelectronic dual function. If PMMA is used as the matrix, Eu-MOF, Pb-MOF, and CNTs are assembled into two Janus fibers respectively, resulting in [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fibers. This avoids the influence of dark-colored conductive materials on the luminescent properties of the luminescent material, while ensuring the continuity of the conductive material in the matrix, thus exhibiting strong conductivity. Therefore, for a single Janus fiber, it exhibits strong conductivity along the fiber length direction due to the continuous conductive network formed by the conductive CNTs in the PMMA matrix. However, in the direction perpendicular to the fiber length, i.e., the fiber diameter direction, it exhibits strong insulation due to the insertion of non-conductive Pb-MOF / Eu-MOF / PMMA fibers, giving Janus fibers microscopic anisotropic conductivity. If a special receiving device is used to orient the Janus fibers as building blocks, [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] can be obtained. Janus fiber array membrane: The resulting array membrane has strong conductivity along the fiber length direction and strong insulation along the direction perpendicular to the fiber length direction, i.e., the fiber diameter direction, which makes the array membrane have strong anisotropic conductivity and at the same time endows it with red fluorescence, resulting in a red fluorescent anisotropic conductive membrane. This membrane material is both a multifunctional material and an advanced anisotropic conductive material.If a CsBr aqueous solution is used as ink to print a QR code on the surface of the array film, the CsBr reacts with Pb-MOF to generate CsPbBr3 quantum dots. Under 365 nm ultraviolet light, the array film itself does not emit light, while the CsPbBr3 quantum dots emit bright green fluorescence, displaying the QR code structure. Scanning the QR code with a smartphone allows the reader to read the information, achieving optical information storage encryption. If a CsBr aqueous solution is used as ink, different patterns, numbers, and letters are screen-printed on the surface of the array film. Under 365 nm ultraviolet light, the array film itself does not emit light, while these patterns, numbers, and letters emit bright green fluorescence. Under 254 nm (or 272 nm) ultraviolet light, the array film itself emits red fluorescence, while the patterns, numbers, and letters printed on its surface emit light green fluorescence, achieving dual-wavelength optical anti-counterfeiting. This array film has anisotropic conductivity, and under 254 nm (or 272 nm) ultraviolet light, it emits light green fluorescence. Under ultraviolet light irradiation at 365 nm, the array film itself emits red fluorescence, while the patterns, numbers, and letters printed on its surface emit a lighter green fluorescence. However, under ultraviolet light irradiation at 365 nm, the array film itself does not emit light, while the patterns, numbers, and letters printed on its surface emit a bright green fluorescence, achieving triple anti-counterfeiting through dual wavelengths and anisotropic conductivity. This special film material has significant application prospects in the electronics industry, medical diagnosis and treatment, electromagnetic interference shielding, multifunctional devices, anti-counterfeiting, and information storage encryption. Currently, no relevant literature reports have been found.
[0007] US Patent No. 1975504 discloses a technical solution for electrospinning (also known as electrospinning technology or electrospinning technique), which is an effective method for preparing continuous micro / nanofibers with macroscopic lengths. It was first proposed by Formals in 1934. This method is mainly used to prepare polymer nanofibers. Its characteristic is that a charged polymer solution or melt is drawn out of a nozzle by electrostatic force in an electrostatic field and projected onto a receiving screen on the opposite side, thus achieving fiber drawing. Then, the solvent evaporates at room temperature, or the melt cools to room temperature and solidifies, obtaining micro / nanofibers. These fibers accumulate to form micro / nanofiber membranes. Uniaxial electrospinning technology has been used to prepare single-function and dual-function optical / electrical nanofiber membranes. QZ Yu, et al. prepared a polyaniline (PANI) nanofiber membrane with a single conductive function using electrospinning technology. Mater. Sci. Eng. B [, 2008, 150, 70-76]; Dong Xiangting et al. prepared PAN / Eu(BA)3phen luminescent nanofibers with a single luminescent function using electrospinning technology [ New Chemical Materials, 2008, 36(9), 49-52]; Dong Xiangting et al. prepared Eu(BA)3phen / PANI / PVP optoelectronic bifunctional composite nanofibers using electrospinning technology [ Journal of Chemical Engineering of Chinese Universities , 2012, 33(8), 1657-1662]; Dong Xiangting et al. used two parallel spinning spinnerets to prepare [nanofibers] / / [nanofibers] type magneto-optical bifunctional Janus nanofibers using electrospinning technology. Chemical Engineering Journal 2014, 254, 259-267]; Liu Tianxi et al. of Fudan University prepared anisotropic conductive films composed of nanofibers using uniaxial electrospinning technology. Nanoscale [2015, 7, 1037-1046]. Currently, there are no reports on the construction of [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array membranes using biaxial parallel electrospinning technology.
[0008] When preparing multifunctional fiber materials using electrospinning technology, the type of raw materials, the molecular weight of the polymer template agent, the composition of the spinning solution, the spinning process parameters, and the structure of the spinneret all have a significant impact on the morphology and size of the final product. This invention employs biaxial parallel electrospinning technology. The spinneret consists of two 12# truncated syringe needles of the same diameter, fixed side-by-side, and then covered with a plastic spray gun head for further fixation, forming a biaxial parallel spinneret that disperses Eu-MOF and Pb-MOF to... N,N A spinning solution I with red fluorescence was prepared by dissolving a mixture of dimethylformamide (DMF) and chloroform (CHCl3) in a solvent followed by the addition of PMMA. Carbon nanotubes (CNTs) were dispersed in the same solvent, and then PMMA was added. This resulted in a spinning solution II with a certain viscosity and electrical conductivity. Spinning solutions I and II were then added to two syringes connected to a biaxial parallel spinneret, which was connected to the positive terminal of a high-voltage power supply. A grounded rotating drum was used as the receiving device. Spinning was performed under optimal conditions using biaxial parallel electrospinning technology to prepare a [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array film. This array film is a red fluorescent anisotropic conductive film with anti-counterfeiting and information encryption capabilities, exhibiting excellent red fluorescence, anisotropic conductivity, anti-counterfeiting, and information storage encryption properties, demonstrating significant application potential. Summary of the Invention
[0009] In the background art, single-functional and bifunctional optical / electrical nanofibers and anisotropic conductive films were prepared using uniaxial electrospinning technology; magneto-optical bifunctional Janus nanofibers of the [nanofiber] / / [nanofiber] type were prepared using electrospinning with two parallel spinnerets. The raw materials, template agents, solvents, and final target products used differ from the method of this invention. This invention employs a specially designed and manufactured biaxial parallel spinning spinneret and an aluminum rotary drum as the receiving device, utilizing biaxial parallel electrospinning technology to prepare a [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array film. This array film is a red fluorescent anisotropic conductive film capable of anti-counterfeiting and information encryption, adding a new material with unique properties to the field of fiber materials.
[0010] This invention is achieved as follows: First, Eu-MOF and Pb-MOF are prepared by precipitation method, and polymethyl methacrylate (PMMA) is prepared by bulk polymerization; Eu-MOF and Pb-MOF are then dispersed into... N,N A spinning solution I with a certain viscosity was obtained by dissolving a mixture of dimethylformamide (DMF) and chloroform (CHCl3) in a solvent, followed by the addition of PMMA. Carbon nanotubes (CNTs) were dispersed in the same solvent, and then PMMA was added to dissolve the CNTs, resulting in a spinning solution II with a certain viscosity. Spinning solutions I and II were then added to two syringes connected to a biaxial parallel spinneret, which was connected to the positive terminal of a high-voltage power supply. A grounded rotating drum was used as the receiving device. Spinning was performed under optimal conditions using biaxial parallel electrospinning technology to prepare a [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array film. This array film is a red fluorescent anisotropic conductive film capable of anti-counterfeiting and information encryption. The steps are as follows: (1) Preparation of Eu-MOF by precipitation method 1.5 mmol Eu2O3 was weighed and dissolved in concentrated nitric acid. The solution was heated and evaporated to obtain Eu(NO3)3·6H2O powder. The powder was dissolved in 80 mL of deionized water to obtain Eu(NO3)3 solution. 1.5 mmol pyromellitic acid H4BTC was dissolved in 250 mL of deionized water. The Eu(NO3)3 solution was slowly added dropwise to the H4BTC solution. The pH of the solution was adjusted to 4-6 using NH3·H2O. The solution was stirred at 75 °C for 24 h to obtain a white precipitate. The precipitate was centrifuged and washed three times with deionized water and ethanol, respectively. The precipitate was dried at 60 °C for 24 h to obtain Eu-MOF. (2) Preparation of Pb-MOF by precipitation method 1.25 mmol Pb(CH3COO)2·3H2O was dissolved in 100 mL of deionized water to obtain a Pb(CH3COO)2 solution. 2.5 mmol of trimesic acid (H3BTC) was dissolved in 200 mL of deionized water to obtain an H3BTC solution. The Pb(CH3COO)2 solution was slowly added dropwise to the H3BTC solution, and the mixture was stirred at room temperature for 12 h to obtain a white precipitate. The precipitate was centrifuged, washed three times with deionized water and ethanol, and dried at 60 °C for 24 h to obtain Pb-MOF. (3) Preparation of polymethyl methacrylate (PMMA) by bulk polymerization Weigh 100 g of methyl methacrylate (MMA) and 0.1 g of benzoyl peroxide (BPO), add them to a 250 mL three-necked flask equipped with a reflux device, and stir until homogeneous. The solution is vigorously stirred and refluxed at 100 °C until it reaches a certain viscosity. When the viscosity is similar to that of glycerol, heating is stopped while continuing stirring, and the solution is allowed to cool naturally to room temperature. The solution is then poured into test tubes to a height of 5-7 cm. After pouring, the solution is allowed to stand for 3 days until no air bubbles remain in the test tubes. The test tubes are then transferred to a 45 °C drying oven and placed for 48 h. The liquid in the test tubes hardens into a transparent solid. Finally, the temperature of the drying oven is increased to 110 °C and maintained for 3 h to complete the polymerization reaction. The solution is then allowed to cool naturally to room temperature to obtain polymethyl methacrylate (PMMA). (4) Preparation of spinning solution 0.3 g Eu-MOF and 1.0 g Pb-MOF were dispersed in a mixed solvent consisting of 3.0 g DMF and 16.0 g CHCl3, and then 1.0 g PMMA was added. The mixture was magnetically stirred at room temperature for 12 h to obtain spinning solution I. 0.05 g CNTs were dispersed in a mixed solvent consisting of 3.0 g DMF and 16.0 g CHCl3, and then 1.0 g PMMA was added. The mixture was magnetically stirred at room temperature for 12 h to obtain spinning solution II. (5) Preparation of [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array membrane by biaxial parallel electrospinning technology Two 10 mL syringes, each with a flattened #12 stainless steel needle, were used. The needles were bent at a 30° angle, ensuring their tips were close together and on the same plane, and then secured with copper wire. A 1 mL plastic spray gun head was then fitted over the two parallel stainless steel needles, with the tips positioned in the middle of the spray gun head, and then fixed in place, forming a dual-axis parallel spinneret. Two spinning solutions were injected into the two syringes respectively, using a vertical spray method. The receiving device was a horizontally placed cylindrical aluminum drum, 20 cm long and 7 cm in diameter, rotating at 1000 r / min. The spinning voltage was 10 kV, the distance between the spray gun tip and the drum was 8 cm, and the ambient temperature was 18°C. o C-25 o At C, with a relative humidity of 20%-25%, electrospinning yields a [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array film, which is a red fluorescent anisotropic conductive film capable of anti-counterfeiting and information encryption.
[0011] The [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array membrane prepared in the above process is composed of oriented Janus fibers, each Janus fiber consisting of two fibers adhered side by side. The average diameter of the Janus fibers is 2.91 ± 0.02 μm. Under 272 nm ultraviolet light excitation, the array membrane emits bright red fluorescence. The surface of the Janus fiber array membrane exhibits strong conductivity along the fiber length direction, with an average conductivity of 7.89 × 10⁻⁶. -5 S·cm -1 However, conductivity is weak along the direction perpendicular to the fiber length, i.e., the fiber diameter direction, with an average conductivity of 1.59 × 10⁻⁶. - 10 S·cm -1 The ratio of conductivity in the two directions is 4.96 × 10⁻⁶. 5It exhibits excellent anisotropic conductivity. When CsBr aqueous solution is used as ink, and a QR code is printed on the surface of the array film using a mold, CsBr reacts with Pb-MOF to generate CsPbBr3 quantum dots. Thus, the QR code pattern contains both CsPbBr3 quantum dots and Eu-MOF. Under 365 nm ultraviolet light, Eu-MOF does not emit light, while CsPbBr3 quantum dots emit bright green fluorescence. This causes the array film itself to not emit light, while the QR code area emits bright green fluorescence, revealing the QR code structure. Scanning the QR code with a smartphone allows the reader to access its information. When irradiated with 254 nm ultraviolet light (replacing 272 nm), the QR code pattern shows a different pattern. Even under ultraviolet light of 365 nm (because ultraviolet lamps of this wavelength are unavailable), Eu-MOF still emits red light, and CsPbBr3 quantum dots still emit green light, causing the array film itself to emit red light and the QR code structure to emit light green fluorescence. However, the information can still be read by a smartphone. When exposed to natural sunlight without ultraviolet light, the smartphone cannot read the QR code information, thus achieving optical information storage encryption. When using CsBr aqueous solution as ink, different patterns or numbers and letters are printed on the surface of the array film using screen printing. Under 365 nm ultraviolet light, the array film itself does not emit light, but the patterns, numbers, and letters emit bright green fluorescence. Under 254 nm ultraviolet light, the array film itself emits red fluorescence, while the printed patterns, numbers, and letters on its surface emit light green fluorescence, achieving dual-wavelength optical anti-counterfeiting. This array film has anisotropic conductivity; under 254 nm ultraviolet light, the array film itself emits red fluorescence, while the printed patterns, numbers, and letters on its surface emit light green fluorescence, but under 365 nm ultraviolet light... Under ultraviolet light irradiation at nm, the array film itself does not emit light, but the patterns, numbers and letters printed on its surface emit bright green fluorescence, achieving triple anti-counterfeiting through dual wavelengths and anisotropic conductivity; the prepared Janus fiber array film has good red fluorescence, anisotropic conductivity, anti-counterfeiting and information encryption functions, thus achieving the purpose of the invention. Attached Figure Description
[0012] Figure 1 This is the XRD pattern of the [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array membrane; Figure 2 This is a SEM image of a [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array membrane, which also serves as an appendix to the abstract. Figure 3 This is a histogram of the diameter distribution of Janus fibers in a [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array membrane. Figure 4 This is an EDS line scan analysis of a single [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber; Figure 5 This is the excitation spectrum of the [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array membrane; Figure 6 This is the emission spectrum of the [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array membrane; Figure 7 This is the CIE chromaticity coordinate diagram of the [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array membrane; Figure 8 This is a diagram illustrating the process of using QR codes to encrypt and store optical information in Janus fiber array films [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA]. Figure 9 This is a diagram illustrating the optical anti-counterfeiting process using astronaut cartoon images for the [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array film. Figure 10 This is a diagram illustrating the digital optical anti-counterfeiting process of [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array film. Detailed Implementation
[0014] The europium oxide (Eu₂O₃) used in this invention has a purity of 99.99%. N,N Dimethylformamide (DMF), chloroform (CHCl3), nitric acid, anhydrous ethanol, ammonia, Pb(CH3COO)2·3H2O, pyromellitic acid (H4BTC), pyromellitic tricarboxylic acid (H3BTC), methyl methacrylate (MMA), and benzoyl peroxide were all commercially available analytical grade products; deionized water was prepared in the laboratory; the glassware and equipment used were commonly used in laboratories.
[0015] Example: 1.5 mmol Eu2O3 was dissolved in concentrated nitric acid and evaporated by heating to obtain Eu(NO3)3·6H2O powder. This powder was then dissolved in 80 mL of deionized water to obtain an Eu(NO3)3 solution. 1.5 mmol pyromellitic acid (H4BTC) was dissolved in 250 mL of deionized water. The Eu(NO3)3 solution was slowly added dropwise to the H4BTC solution. The pH of the solution was adjusted to 4-6 using NH3·H2O. The mixture was stirred at 75 °C for 24 h to obtain a white precipitate. The precipitate was centrifuged and washed three times with deionized water and ethanol, respectively, and dried at 60 °C for 24 h to obtain Eu-MOF. 1.25 mmol Pb(CH3COO)2·3H2O was dissolved in 100 mL of deionized water to obtain a Pb(CH3COO)2 solution. 2.5 mmol pyromellitic acid (H3BTC) was dissolved in 200 mL of deionized water to obtain a Pb(CH3COO)2 solution. H3BTC solution was obtained from deionized water. Pb(CH3COO)2 solution was slowly added dropwise to the H3BTC solution, and the mixture was stirred at room temperature for 12 h to obtain a white precipitate. The precipitate was centrifuged and washed three times with deionized water and ethanol, respectively, and dried at 60 °C for 24 h to obtain Pb-MOF. 100 g of methyl methacrylate (MMA) and 0.1 g of benzoyl peroxide (BPO) were weighed and added to a 250 mL three-necked flask equipped with a reflux device and stirred evenly. The solution was vigorously stirred and refluxed at 100 °C until it reached a certain viscosity. When the viscosity was similar to that of glycerol, the heating was stopped while stirring continued and the solution was allowed to cool naturally to room temperature. The solution was then poured into test tubes to a height of 5-7 cm. After pouring, the solution was allowed to stand for 3 days until no air bubbles remained in the test tubes. The test tubes were then transferred to a 45 °C drying oven and placed for 48 h. The liquid in the test tubes hardened into a transparent solid. Finally, the temperature of the drying oven was increased to 110 °C and maintained for 3 hours. The polymerization reaction was allowed to stop at h, and then the mixture was allowed to cool naturally to room temperature to obtain polymethyl methacrylate (PMMA). 0.3 g Eu-MOF and 1.0 g Pb-MOF were dispersed in a mixed solvent consisting of 3.0 g DMF and 16.0 g CHCl3, and then 1.0 g PMMA was added. The mixture was magnetically stirred at room temperature for 12 h to obtain spinning solution I. 0.05 g CNTs were dispersed in a mixed solvent consisting of 3.0 g DMF and 16.0 g CHCl3, and then 1.0 g PMMA was added.0 g PMMA was magnetically stirred at room temperature for 12 h to obtain spinning solution II. Two 10 mL syringes, each with a truncated 12# stainless steel needle, were used. The two stainless steel needles were bent at a 30º angle so that their tips were closely adjacent and on the same plane, and then fixed with copper wire. Finally, a 1 mL plastic spray gun head was placed over the two parallel stainless steel needles, with the tips of the two stainless steel needles in the middle of the plastic spray gun head, and then fixed to form a biaxial parallel spinneret. The two spinning solutions were injected into the two syringes respectively, using a vertical spray method. The receiving device was a horizontally placed cylindrical aluminum drum with a length of 20 cm and a diameter of 7 cm, with a rotation speed of 1000 r / min, a spinning voltage of 10 kV, a distance of 8 cm between the tip of the spray gun head and the drum, and an ambient temperature of 18°C. o C-25 o At temperature C, relative humidity of 20%-25%, electrospinning yields a [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array film. This array film is a red fluorescent anisotropic conductive film capable of anti-counterfeiting and information encryption. The [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array film contains Eu-MOF and Pb-MOF, see [link to documentation]. Figure 1 As shown; in the [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array membrane, the Janus fibers are oriented to form an array, see Figure 2 As shown; the average diameter of the Janus fibers in the [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array membrane is 2.91±0.02 μm, see Figure 3 As shown; Eu and Pb elements represent Eu-MOF and Pb-MOF, respectively. EDS line scan analysis of a single Janus fiber shows that Eu and Pb elements are only present on the left half of the Janus fiber. This analytical result is consistent with the structure of the Janus fiber. (See...) Figure 4 As shown; using 615 nm as the monitoring wavelength, the [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array film exhibits a broad excitation band in the 200-350 nm range, with a peak at 272 nm, which can be attributed to the π→π* transition of the ligands. There is no excitation peak at 365 nm, indicating that 365 nm UV light cannot excite the sample to produce red fluorescence, while 254 nm UV light can excite the sample to produce red fluorescence. (See...) Figure 5As shown; under 272 nm ultraviolet light excitation, the emission peaks of the [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array film are located at 592 nm and 615 nm, corresponding to the Eu emission peaks. 3+ of 5 D0→ 7 F1 and 5 D0→ 7 F2 level transition, see Figure 6 As shown; under 272 nm ultraviolet light excitation, the [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array film emits bright red light with chromaticity coordinates of (0.6212, 0.3477). Figure 7 As shown; the Janus fiber array membrane exhibits strong conductivity along the fiber length direction on its surface, with an average conductivity of 7.89 × 10⁻⁶. -5 S·cm -1 However, conductivity is weak along the direction perpendicular to the fiber length, i.e., the fiber diameter direction, with an average conductivity of 1.59 × 10⁻⁶. -10 S·cm -1 The ratio of conductivity in the two directions is 4.96 × 10⁻⁶. 5 It exhibits excellent anisotropic conductivity. When CsBr aqueous solution is used as ink, and a QR code is printed on the surface of the array film using a mold, CsBr reacts with Pb-MOF to generate CsPbBr3 quantum dots. Thus, the QR code pattern contains both CsPbBr3 quantum dots and Eu-MOF. Under 365 nm ultraviolet light, Eu-MOF does not emit light, while CsPbBr3 quantum dots emit bright green fluorescence. This causes the array film itself to not emit light, while the QR code area emits bright green fluorescence, revealing the QR code structure. Scanning the QR code with a smartphone allows the reader to access its information. When irradiated with 254 nm ultraviolet light (replacing 272 nm), the QR code pattern becomes more transparent. Even under ultraviolet light of nm (because ultraviolet lamps of this wavelength are unavailable), Eu-MOF can still emit red light, and CsPbBr3 quantum dots can still emit green light, causing the array film itself to emit red light. The QR code structure emits light green fluorescence, but the information can still be read by a smartphone. When there is no ultraviolet light and only natural sunlight, the smartphone cannot read the QR code information, thus achieving optical information storage encryption. See Figure 8 As shown; when CsBr aqueous solution is used as ink, and astronaut cartoon images are screen-printed onto the surface of the array film, under 365 nm ultraviolet light irradiation, the array film itself does not emit light, while the astronaut cartoon image emits bright green fluorescence. Under 254 nm ultraviolet light irradiation, the array film itself emits red fluorescence, while the astronaut cartoon image on its surface emits light green fluorescence, achieving dual-wavelength optical anti-counterfeiting; see Figure 9 As shown; when CsBr aqueous solution is used as ink, and numbers are screen-printed onto the surface of the array film, under 365 nm ultraviolet light irradiation, the array film itself does not emit light, while the numbers emit bright green fluorescence. Under 254 nm ultraviolet light irradiation, the array film itself emits red fluorescence, while the numbers on its surface emit light green fluorescence, achieving dual-wavelength optical anti-counterfeiting. Figure 10 As shown, the array film exhibits anisotropic conductivity. Under 254 nm ultraviolet light irradiation, the array film itself emits red fluorescence, while the pattern printed on its surface emits light green fluorescence. However, under 365 nm ultraviolet light irradiation, the array film itself does not emit light, while the pattern printed on its surface emits bright green fluorescence, achieving triple anti-counterfeiting through dual wavelengths and anisotropic conductivity. The [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array film described above possesses excellent red fluorescence, anisotropic conductivity, anti-counterfeiting, and information encryption functions.
[0016] Of course, the present invention may have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications according to the present invention, but these corresponding changes and modifications should all fall within the protection scope of the appended claims.
Claims
1. A red fluorescent anisotropic conductive film capable of anti-counterfeiting and information encryption, characterized in that, Composed of oriented Janus fibers, it has good red fluorescence, anisotropic conductivity, anti-counterfeiting and information encryption functions; the average diameter of Janus fibers is 2.91±0.02 μm.
2. A method for preparing a red fluorescent anisotropic conductive film with anti-counterfeiting and information encryption capabilities as described in claim 1, characterized in that, Electrospinning technology is employed, using a dual-axis parallel spinneret to achieve the desired spinning effect. N,N Using dimethylformamide (DMF) and chloroform (CHCl3) as a mixed solvent, and polymethyl methacrylate (PMMA) as a spinning template and matrix, a [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array membrane was prepared. The steps were as follows: (1) Preparation of Eu-MOF by precipitation method 1.5 mmol Eu2O3 was weighed and dissolved in concentrated nitric acid. The solution was heated and evaporated to obtain Eu(NO3)3·6H2O powder. The powder was dissolved in 80 mL of deionized water to obtain Eu(NO3)3 solution. 1.5 mmol pyromellitic acid H4BTC was dissolved in 250 mL of deionized water. The Eu(NO3)3 solution was slowly added dropwise to the H4BTC solution. The pH of the solution was adjusted to 4-6 using NH3·H2O. The solution was stirred at 75 °C for 24 h to obtain a white precipitate. The precipitate was centrifuged and washed three times with deionized water and ethanol, respectively. The precipitate was dried at 60 °C for 24 h to obtain Eu-MOF. (2) Preparation of Pb-MOF by precipitation method 1.25 mmol Pb(CH3COO)2·3H2O was dissolved in 100 mL of deionized water to obtain a Pb(CH3COO)2 solution. 2.5 mmol of trimesic acid (H3BTC) was dissolved in 200 mL of deionized water to obtain an H3BTC solution. The Pb(CH3COO)2 solution was slowly added dropwise to the H3BTC solution, and the mixture was stirred at room temperature for 12 h to obtain a white precipitate. The precipitate was centrifuged, washed three times with deionized water and ethanol, and dried at 60 °C for 24 h to obtain Pb-MOF. (3) Preparation of polymethyl methacrylate (PMMA) by bulk polymerization Weigh 100 g of methyl methacrylate (MMA) and 0.1 g of benzoyl peroxide (BPO), add them to a 250 mL three-necked flask equipped with a reflux device, and stir until homogeneous. The solution is vigorously stirred and refluxed at 100 °C until it reaches a certain viscosity. When the viscosity is similar to that of glycerol, heating is stopped while continuing stirring, and the solution is allowed to cool naturally to room temperature. The solution is then poured into test tubes to a height of 5-7 cm. After pouring, the solution is allowed to stand for 3 days until no air bubbles remain in the test tubes. The test tubes are then transferred to a 45 °C drying oven and placed for 48 h. The liquid in the test tubes hardens into a transparent solid. Finally, the temperature of the drying oven is increased to 110 °C and maintained for 3 h to complete the polymerization reaction. The solution is then allowed to cool naturally to room temperature to obtain polymethyl methacrylate (PMMA). (4) Preparation of spinning solution 0.3 g Eu-MOF and 1.0 g Pb-MOF were dispersed in a mixed solvent consisting of 3.0 g DMF and 16.0 g CHCl3, and then 1.0 g PMMA was added. The mixture was magnetically stirred at room temperature for 12 h to obtain spinning solution I. 0.05 g CNTs were dispersed in a mixed solvent consisting of 3.0 g DMF and 16.0 g CHCl3, and then 1.0 g PMMA was added. The mixture was magnetically stirred at room temperature for 12 h to obtain spinning solution II. (5) Preparation of [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array membrane by biaxial parallel electrospinning technology Two 10 mL syringes, each with a flattened #12 stainless steel needle, were used. The two needles were bent at a 30° angle, ensuring their tips were close together and on the same plane, and then secured with copper wire. A 1 mL plastic spray gun head was then fitted over the two parallel stainless steel needles, with the tips positioned in the middle of the spray gun head, and then fixed in place, forming a dual-axis parallel spinneret. Two spinning solutions were injected into the two syringes respectively, using a vertical spray method. The receiving device was a horizontally placed cylindrical aluminum drum, 20 cm long and 7 cm in diameter, rotating at 1000 r / min. The spinning voltage was 10 kV, the distance between the spray gun tip and the drum was 8 cm, and the ambient temperature was 18°C. o C-25 o At a relative humidity of 20%-25%, electrospinning yields a [Pb-MOF / Eu-MOF / PMMA] / / [CNTs / PMMA] Janus fiber array film. This array film is a red fluorescent anisotropic conductive film capable of anti-counterfeiting and information encryption. It consists of oriented Janus fibers, each composed of two fibers adhered side-by-side. The average diameter of the Janus fibers is 2.91±0.02 μm. Under 272 nm ultraviolet light excitation, the array film emits bright red fluorescence. The Janus fiber array film exhibits strong conductivity along the fiber length direction on its surface, with an average conductivity of 7.89×10⁻⁶. -5 S·cm -1 However, conductivity is weak along the direction perpendicular to the fiber length, i.e., the fiber diameter direction, with an average conductivity of 1.59 × 10⁻⁶. -10 S·cm -1 The ratio of conductivity in the two directions is 4.96 × 10⁻⁶. 5 It exhibits excellent anisotropic conductivity. When CsBr aqueous solution is used as ink, and a QR code is printed on the surface of the array film using a mold, CsBr reacts with Pb-MOF to generate CsPbBr3 quantum dots. Thus, the QR code pattern contains both CsPbBr3 quantum dots and Eu-MOF. Under 365 nm ultraviolet light, Eu-MOF does not emit light, while CsPbBr3 quantum dots emit bright green fluorescence. This causes the array film itself to not emit light, while the QR code area emits bright green fluorescence, revealing the QR code structure. Scanning the QR code with a smartphone allows the reader to access its information. When irradiated with 254 nm ultraviolet light (replacing 272 nm), the QR code pattern shows a different pattern. Even under ultraviolet light of 365 nm (because ultraviolet lamps of this wavelength are unavailable), Eu-MOF still emits red light, and CsPbBr3 quantum dots still emit green light, causing the array film itself to emit red light and the QR code structure to emit light green fluorescence. However, the information can still be read by a smartphone. When exposed to natural sunlight without ultraviolet light, the smartphone cannot read the QR code information, thus achieving optical information storage encryption. When using CsBr aqueous solution as ink, different patterns or numbers and letters are printed on the surface of the array film using screen printing. Under 365 nm ultraviolet light, the array film itself does not emit light, but the patterns, numbers, and letters emit bright green fluorescence. Under 254 nm ultraviolet light, the array film itself emits red fluorescence, while the printed patterns, numbers, and letters on its surface emit light green fluorescence, achieving dual-wavelength optical anti-counterfeiting. This array film has anisotropic conductivity; under 254 nm ultraviolet light, the array film itself emits red fluorescence, while the printed patterns, numbers, and letters on its surface emit light green fluorescence, but under 365 nm ultraviolet light... Under ultraviolet light irradiation at nm, the array film itself does not emit light, but the patterns, numbers and letters printed on its surface emit bright green fluorescence, achieving triple anti-counterfeiting with dual wavelengths and anisotropic conductivity; the prepared Janus fiber array film has good red fluorescence, anisotropic conductivity, anti-counterfeiting and information encryption functions.
Citation Information
Patent Citations
Process and apparatus for preparing artificial threads
US1975504A
